Voltammetric and electrochemical impedimetric behavior of silica-based gel electrolyte for valve-regulated lead-acid battery - Gencten, Metin; Donmez, Koray B.; Sahin, Yucel; Pekmez, Kadir; Suvaci, Ender (SPRINGER, 2014)
The gel electrolyte is an important component of the valve-regulated lead-acid (VRLA) batteries. In this study, fumed silica-based gel electrolyte systems were prepared. In this concept, several important parameters controlling the performance of the GEL-VRLA battery, such as the sulfuric acid and fumed silica concentrations, gel formulation, gelling time and rate, and different additives (Na2SO4 and MgSO4), were scientifically investigated. The gel formulations were characterized by cyclic voltammetric and electrochemical impedance spectroscopic methods. The optimum parameters were determined by using the results of anodic peak currents and redox capacities, R (s) and R (ct) values. Addition of 6 % (w/w) fumed silica to 30 % (w/w) sulfuric acid, for preparation of gelled electrolyte, increased the battery performance significantly. According to the results of the transmission electron and optic microscope images of the gel electrolytes, the three-dimensional gel structure was prepared successfully. The optimization of sulfuric acid concentration and amount of Na2SO4 and MgSO4 additives were examined for the first time in detail by cyclic voltammetry, electrochemical impedimetry, and battery test. Na2SO4 and MgSO4 additives make a good combination with a gelled-electrolyte system and improve the charge/discharge capacity according to sulfuric acid electrolytes. According to the experimental results, the fumed silica-based gel electrolyte system has a great potential for application in gelled electrolyte VRLA batteries.
Keywords: Gel electrolyte; Cyclic voltammetry; Electrochemical impedance spectroscopy; Valve-regulated lead-acid (VRLA) batteries; Fumed silica; PARTIAL-STATE; PERFORMANCE; ADDITIVES; DISCHARGE; SILOXANE; WORKING; PLATES; Electrochemistry